TRANSFORMASI PROSES BISNIS SERTA PENGARUHNYA TERHADAP KINERJA PEMASARAN USAHA KECIL DAN MENENGAH SUTRA WAJO DI SULAWESI SELATAN - Awaluddin, Murtiadi; Sijal, Mutakallim; Sylvana, Andi (Universitas Islam Negeri Alauddin Makassar, 2024)
The aims of this research are to determine : (1) the influence of business process orientation on customer orientation and competitor orientation in small and medium silk businesses; (2) the influence of customer orientation and competitor orientation on innovation orientation in small and medium silk businesses; (3) the influence of innovation orientation on the marketing performance of small and medium silk enterprises; (4) the influence of business process orientation on innovation orientation through customer orientation and competitor orientation in small and medium silk enterprises; (5) the influence of business process orientation on marketing performance through customer orientation, competitor orientation and innovation orientation in small and medium silk businesses. The sampling technique used purposive sampling.Sample size plays an important role in estimating and interpreting the results of Structural Equation Modeling (SEM) analysis, with the estimation model using maximum likelihood (ML), so the number of samples determined in thisstudy was 160 respondents. The analytical method used in this research is structural equation modeling (SEM). The conclusions of this research are as follows:(1) business process orientation has a positive and significant effect on customer orientation and competitor orientation in small and medium silk businesses; (2) customer orientation and competitor orientation have a positive and significant effect on innovation orientation in small and medium silk businesses; (3) innovation orientation has a positive and significant effect on the marketing performance of small and medium silk enterprises; (4) business process orientation has a positive and significant effect on innovation orientation through customer orientation and competitor orientation in small and medium silk businesses; (5) business process orientation has a positive and significant effect on marketing performance through customer orientation, competitor orientation and innovation orientation in small and medium silk businesses.